Aligning Project Management with Business Strategy - Al Sabaa, Amena Yousef (2010)
Business strategy is becoming a subject of very high importance in business environments. Business strategy defines organization objects and goals in long term plan. In order to compete in business markets, business strategy should be executed successfully. Project management is a critical tool. It has direct effect on business strategy. If used in mature way, business strategy will be achieved with significant outcomes. But if it goes in different direction than the business strategy, lot of negative consequences will result. It is not enough to complete the project successfully; it has to achieve benefits and be part of the business strategy. Lot of methodologies and frameworks has been introduced with different elements to ensure project management alignment with business strategy such as Portfolio Management. The long term goals must be achieved by selecting the right projects and managing them consistently. This paper defines the newly emerged concept of aligning project management with business strategy. The topics presented include: business strategy effectiveness, project management practices, project managers capabilities, alignment framework. Case studies are also included. These cases are analyzed to investigate the effect of project management alignment with business strategy in the business environment. The research is also including recommendation on applying successful alignment model. Finally, conclusions are drawn based on discussed topics.